DESKRIPSI KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMPN 17 KOTA JAMBI - Aisyah Aisyah (Jurnal Ilmiah Dikdaya, 2018)
The ability of mathematical communication includes two things namely the ability of students to use mathematics as a means of communication (language of mathematics), and the ability to communicate the mathematics learned. The indicators of mathematical communication abilities are: 1) Written Text, which provides answers using its own language, modeling situations or problems using writing, graphics and algebra, explaining or describing mathematical concepts that have been studied, making conjectures, formulating arguments and generalizations; 2) Drawing, ie reflecting real objects, drawings and diagrams into mathematical ideas; 3) Mathematical Expression, ie expressing mathematical concepts by declaring them in language or mathematical symbols. The formulation of the problem in this research is how is the communication skill matemats of students of class IX SMPN 17 Kota Jambi? While the purpose of this study is to describe the mathematical communication skills of class IX students SMPN 17 Kota Jambi. This research includes the type of qualitative research that uses descriptive qualitative research methodology. While the subject of the study is the students of class IX A SMPN 17 Kota Jambi. Data collection techniques conducted in this study include tests, documentation, and interviews. Furthermore, data analysis techniques performed are 1) data reduction (data reduction); 2) display data (data exposure/ categorization); and 3) conclusion drawing/verification (withdrawal). Keyword: Description, Ability of Mathematical Communication